Sulfur–Carbon Bond Formation through Ring‐Opening of Triazolothiadiazole with Organometallics. Issue 15 (8th April 2014) - Othman, Raja Ben; Massip, Stéphane; Marchivie, Mathieu; Jarry, Christian; Vercouillie, Johnny; Chalon, Sylvie; Guillaumet, Gérald; Suzenet, Franck; Routier, Sylvain
Abstract: An efficient and convenient method was developed for the formation of S ‐substituted thiotriazoles through an unprecedented organometallic addition and subsequent ring‐opening sequence of 3‐substituted [1, 2, 4]triazolo[3, 4‐ b ][1, 3, 4]thiadiazole. The method is applicable to a wide range of substrates containing different functional groups and furnishes excellent yields of the corresponding N ‐unsubstituted 3‐ or 5‐alkyl, aryl, alkynyl and alkenyl sulfanyl‐1, 2, 4‐triazole products. Abstract : An efficient and convenient method was developed for the formation of S ‐substituted thiotriazoles through an unprecedented organometallic addition and subsequent ring‐opening sequence. A wide range of substrates containing different functional groups were used, and the corresponding N‐unsubstituted 3‐alkyl, aryl, alkynyl and alkenyl sulfanyl‐1, 2, 4‐triazole products were produced.